ANALISIS FAKTOR-FAKTOR RESIKO YANG MEMPENGARUHI KEJADIAN DIARE PADA BALITA DI PUSKESMAS AMBAL 1 KECAMATAN AMBAL KABUPATEN KEBUMEN - ANS, safrudin; -, Handoyo; Widiyanti, Dwi Ayudha Kurnia (Jurnal Ilmiah Kesehatan Keperawatan, 2009)
Low social economic and community situation and also unsupported environment often create diarrhea cases. The diarrhea cases that suffered by the BALITA patients in Ambal Community Health Center were caused by the climate change from rainy to dry season. The aim of this research is to find out diarrhea case factor analyses of BALITA (babies under five years old) patient in Ambal Community Health Center work area, Ambal, Kebumen. The analytic research used cross sectional approach the sample were taken by using purposive sampling based on inclusion criteria. The experiment was done 27 Februari - 28 April 2009. the result of the data showed that there were 23 balitas suffered by diarrhea case and 37 balitas were not suffered by diarrhea case. The result of this study show that: diarrhea case number 38 %. Factor that caused the diarrhea case for BALITA patients in Ambal 1 Community Health Center were:(1) nutrition status (OR=0,391), (2) environment factor (OR=1,6931), (3) economic factor (OR=4,996), (4) food feeding pattern (OR=0,402). Conclusion: The most dominant risk factor that caused diarrhea case of balita patients in Ambal in community Health Center was economical status. Keywords: Risk factors of caused diarrhea, BALITA.